Stage-I Shariah compliant Macaulay's duration model testing. Issue 7 (18th August 2021) - Shah, Syed Alamdar Ali; Sukmana, Raditya; Fianto, Bayu Arie
Abstract : Purpose: The purpose of this study is to develop, test and examine econometric methodology for Sharīʿah-compliant duration models of Islamic banks. Design/methodology/approach: The research evaluates all existing duration models from Sharīʿah's perspective and develops a four-stage framework for testing Sharīʿah-compliant duration models. The econometric methodology consists of multiple regression, Johansen co-integration, error correction model, vector error correction model (VECM) and threshold vector error models (TVECM). Findings: Regressions analysis suggests that returns on earning assets and interbank offered rates are significant factors for calculating the duration of earning assets, whereas returns paid on return bearing liabilities and average interbank rates of deposits are significant factors for duration of return bearing liabilities. VECM suggests that short run duration converges into long run duration and TVECM suggests that management of assets and liabilities also plays a significant role that can bring about a change of about 15% in respective durations. Practical implications: Sharīʿah-compliant duration models will improve risk and Sharīʿah efficiency, which will ultimately improve market capitalization and returns stability of Islamic banks in the long run. Originality/value: Sharīʿah-compliant duration models testing provides insight into how various factors, namely, rates of return, benchmark rates and managerial skills of Islamic bank risk managers impact durations of assets and liabilities. It also explains the future course of action for Sharīʿah-compliant duration model testing.